OCD-FI, On-Chip Debugging and Fault Injection for validating microprocessor based dependable systems - André Vaz Fidalgo (2006)
This paper proposes a set of modifications to the on-chip debugging infrastructures present in many actual microprocessor cores, with the objective of supporting the validation and verification steps of fault-tolerant mechanisms through fault injection campaigns. A synthesisable microprocessor core for programmable components was used as a target system an. a debugging infrastructure compliant with the NEXUS 5001 proposed standard for onchip debugging was implemented on this target. To improve the process of real-time memory fault injection, an upgraded infrastructure designated as On-Chip Debugging and Fault Injection (OCD-FI) was developed. The complete system was analysed in terms of area overhead and fault injection capabilities and performance. All elements were designed as synthesizable VHDL modules and evaluated in simulation.